The Effect of Selenium Sources and Rates on Cowpea Seed Quality - Pereira, Rhayra Zanol; Fontes, Luiz Eduardo de Morais Fernandes; Silva, Vinícius Martins; Zuffo, Alan Mario; Custódio, Ceci Castilho; Sá, Francisco Vanies da Silva; Reis, André Rodrigues dos [UNESP]; Alves, Charline Zaratin (MDPI, 2024)
Selenium (Se) is a beneficial element for plants and is essential for human nutrition. In plants, it plays an important role in the formation of selenocysteine and selenomethionine and in the activation of hydrolytic enzymes, which can aid in seed germination and reduce abiotic stress during germination. The objective of this study was to evaluate the effects of the application of selenium sources and rates to the soil on the physiological quality of cowpea seeds. The experimental design was a randomized block with four replications and a factorial scheme (7 × 2). Two sources of Se (sodium selenate and sodium selenite) and seven rates (0, 2.5, 5, 10, 20, 40 and 60 g ha−1) were used. Physiological characterization was carried out by first counting of germination, germination, emergence, accelerated aging, cold testing, electrical conductivity, length and dry biomass of shoots and roots. Germination after accelerated aging increased with selenate, even at higher rates, whereas selenite provided benefits at lower rates. Selenation linearly increased germination after the cold test and linearly reduced electrolyte leakage as the Se rate increased. The soil application of Se is beneficial for cowpea seed quality. Compared with those treated with sodium selenite, cowpea plants treated with sodium selenate through the soil produce more vigorous seeds. The application of 10 g ha−1 Se in the form of sodium selenate provides seedlings with faster germination and root development and is an alternative for rapid stand establishment.
Keywords: seed physiological potential; seed vigor; sodium selenate and sodium selenite; soil application; Vigna unguiculataL. Walp